Superorbital variability of the gamma-ray binary LS I +61 303 studied with MAGIC - Paredes, Josep Maria (2015)
The gamma-ray binary LS I +61 303 has been detected from radio up to very high–energy gamma rays. Its emission is likely originated by the interaction of the stellar wind and a relativistic outflow. The broadband emission shows a periodicity of about 26.6 days, coincident with the orbital period. A long-term periodicity of 1667 ± 8 days was discovered in radio and confirmed in optical and high–energy gamma rays. Here we will present the results of a four-year campaign performed by MAGIC together with archival data. In this campaign, we search for a long-term signature in the VHE emission from LS I +61 303. We will focus on the search for super orbital modulation of the VHE emission, similarly to the one observed at other wavelengths, and on the search for (anti-)correlation between the TeV emission and the extension of the circumstellar disk, measured using optical data.